Prevention of strain-induced impairments of patellar tendon micromorphology in adolescent athletes - Mersmann, F.; Domroes, T.; Pentidis, N.; Tsai, M.-S.; Bohm, S.; Schroll, A.; Arampatzis, A. (Scandinavian Journal of Medicine & Science in Sports, 2021)
High-level patellar tendon strain may cause impairments of the tendon's micromorphological integrity in growing athletes and increase the risk for tendinopathy. This study investigated if an evidence-based tendon exercise intervention prevents high-level patellar tendon strain, impairments of micromorphology and pain in adolescent basketball players (male, 13-15 years). At three time points over a season (M1-3), tendon mechanical properties were measured using ultrasound and dynamometry, proximal tendon micromorphology with a spatial frequency analysis and pain and disability using VISA-P scores. The control group (CON, n = 19) followed the usual strength training plan, including sprint and change-of-direction drills. In the intervention group (INT, n = 14), three sessions per week with functional exercises were integrated into the training, providing repetitive high-magnitude tendon loading for at least 3 s per repetition. The frequency of high-level strain (ie, =9%) continuously decreased in INT, while tending to increase in CON since tendon force increased in both (p < 0.001), yet tendon stiffness only in INT (p = 0.004). In CON, tendon strain was inversely associated with tendon peak spatial frequency at all time points (p < 0.05), indicating impairments of tendon micromorphological integrity with higher strain, but not at M2 and M3 in INT. Descriptively, the fraction of asymptomatic athletes at baseline was similar in both groups (~70%) and increased to 100% in M3 in INT, while remaining unchanged in CON. We suggest that functional high-load tendon exercises could reduce the prevalence of high-level patellar tendon strain and associated impairments of its micromorphology in adolescent athletes, providing new opportunities for tendinopathy prevention.